Performative and economic analysis on local duck farming in Central Java - Indonesia - Ismoyowati, I.; Pratama, B. C.; Innayah, M. N. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
Central Java is the region that produces the second largest duck egg production in Indonesia or reaches 13.55% of the total national duck egg production. Therefore, duck farming in Central Java requires an economic evaluation to identify the success of the business. The economic analysis in the duck farm industry will update the latest statistics on production costs, outputs and profitability. This study aims to assess the analysis of laying duck business, which includes: marginal production costs, total net income and input-output ratio of duck egg production in various regions in Central Java, Indonesia. The study was conducted using a survey method using multi-stage sampling involving 120 duck farmers from the regency of Tegal, Brebes, and Pemalang. Each district was taken 40 farms as respondents by purposive random sampling with criteria for the number of breeders who had a minimum duck population of 100 ducks and a production period of 8-12 months. The analytical tools used include descriptive statistics and farm budgetary analysis. This study showed that duck breeders incur large costs to obtain production inputs, especially from feed aspects. Although three regencies reported profit based on the estimated input-output ratios, it is only a marginal profit that amounted to1: 1.382, 1:1.658, and 1:1.433 in Tegal, Brebes, and Pemalang, respectively. The conclusion of the study is the performance of duck farms in Central Java are still profitable even in the smallholder duck farm industry, with the highest profits obtained by farmers in Brebes Regency.